Neoangiogenesis - forming an effective network of blood vessels as a critical determinant of tumor development - Wróbel, Grzegorz; Spałek, Jakub; Zieliński, Paweł (Journal of Education, Health and Sport, 2017)
The development of a tumor in the early stages of growth is associated with the delivery of nutrients and oxygen to the tumor cells by diffusion from the surrounding healthy tissue, while in the later stages, when the tumor size is so large that it begins to lack oxygen and nutrients, comes to neoangiogenesis - the formation of blood vessels in the area of the affected tissue. Tumor vessels are leaky, winding and have a lot of bottlenecks and dead-ends. Abnormalities of blood vessels anatomy determine the deceleration rate and residual blood flow. Tumor vascularization affects its local growth, and in the case of tumors with the potential to distant metastases, the increase vascularity of tumor by increasing the density of the blood vessel network is directly proportional to the risk of distant metastasis. The aim of the study was to summary the role of the formation of tumor blood vessels in the context of the development of tumors.